ASSESSMENT OF THE COMPLEXITY OF COORDINATING SPECIALIZED LOADS IN 15-16 YEAR-OLD FOOTBALL PLAYERS - Bakhodirov, Savar Sirojiddinovich (Mental Enlightenment Scientific-Methodological Journal, 2025)
The article notes that the result of playing football can be improved only with appropriate general and special technical-tactical training, so that all actions are targeted and rational. In football, the actions during the game cannot be predicted and calculated in advance from the point of view of space and time, therefore, most coaches agree that the basis of the players' game actions is technical and tactical preparation.